1989
DOI: 10.1093/ajcn/50.5.1008
|View full text |Cite
|
Sign up to set email alerts
|

Day-long glucose, insulin, and fructose responses of hyperinsulinemic and nonhyperinsulinemic men adapted to diets containing either fructose or high-amylose cornstarch

Abstract: Ten hyperinsulinemic and 11 nonhyperinsulinemic men consumed a typical American diet containing 20% of calories either as fructose or as high-amylose cornstarch for 5 wk in a crossover design to determine their effects on indices of glucose tolerance. Blood glucose, insulin, and fructose were determined before and 30, 60, 90, 120 and 180 min after breakfast, lunch, and dinner. Glucose responses were significantly lower 60 and 120 min and the insulin response lower 60 min after the meals containing fructose. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 35 publications
1
24
0
2
Order By: Relevance
“…However, increases of fasting TG concentrations have been reported after 2 or more weeks of fructose consumption at 15%-20% of energy requirements (13)(14)(15)(16)(17)(18). The reason for these conflicting results is unclear but may be related to the marked within-group and within-individual variability we observed in fasting TG responses to dietary fructose.…”
Section: Figurementioning
confidence: 87%
“…However, increases of fasting TG concentrations have been reported after 2 or more weeks of fructose consumption at 15%-20% of energy requirements (13)(14)(15)(16)(17)(18). The reason for these conflicting results is unclear but may be related to the marked within-group and within-individual variability we observed in fasting TG responses to dietary fructose.…”
Section: Figurementioning
confidence: 87%
“…Noticeably, type 2 diabetic patients are common with obesity and, 150-225 million people worldwide are affected with type 2 diabetes, according to a recent epidemiologic report (Zimmet, 2003). A diet with high sucrose or fructose has been observed to induce insulin resistance, although without clear mechanisms (Hallfrisch et al, 1983;Israel et al, 1983;Reaven, 1991;Reiser et al, 1989). For instance, an increased blood pressure associated with hyperinsulinemia and hypertriglyceridemia in normal Sprague Dawley rats was observed after only 2 weeks on a high fructose (66%) diet (Hwang et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of fructose or sucrose (1 glucose + 1 fructose) sweeteners used in beverages and processed foods has increased significantly in the last two decades. It has been shown that a diet high in fructose or sucrose can increase blood pressure and induce insulin resistance although the mechanism is unclear (Hallfrisch et al, 1983;Israel et al, 1983;Reaven, 1991;Reiser et al, 1989). Significant increase of serum fructose to 12 μM in diabetic patients compared with a level of 8.1 μM in healthy subjects has been reported (Kawasaki et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…After fructose ingestion, several researchers observed blood glucose levels that were reduced compared with levels after starch or sucrose ingestion in diabetic patients (10,(15)(16)(17)(18). Additionally, studies conducted in healthy subjects noted that different amounts of fructose intake did not change HbA 1c levels (19), yet they significantly elevated plasma triglycerides (20).…”
mentioning
confidence: 99%